2002
DOI: 10.1002/ejoc.200390039
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoreactivity of a Chiral Oxathiane Derived from 5‐Hydroxy‐1‐tetralone

Abstract: The diastereoreactivity at the CH 2 bridge of a cis-oxathiane derived from 5-hydroxy-1-tetralone (unprotected and protected at the OH) was studied, and it appeared that all reactions at C-2 provided equatorial substitution. It was also found that: i) reductions of the equatorial benzoyl derivative with selectrides provided high diastereoselectivities at C-2Ј while LAH did not. Methyl Grignard addition was less selective and the selectivity of the propanoyl analogue was smaller; ii) condensation of aldehydes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Moreover, NOE experiments, with positive effects between proton H5 and protons H7 and H3 axial , Figure , showed that the R-groups have equatorial orientation in both oxathianes 4a and 4b, as we already observed in the case of type 2 oxathianes …”
supporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, NOE experiments, with positive effects between proton H5 and protons H7 and H3 axial , Figure , showed that the R-groups have equatorial orientation in both oxathianes 4a and 4b, as we already observed in the case of type 2 oxathianes …”
supporting
confidence: 68%
“…Chiral 1,3-oxathianes 1 − 4 have been used at the SCH 2 O bridge for diastereoselective synthesis of bioactive compounds or at the sulfur atom , as a precursor of chiral ylides. Concerning the reactivity of the SCH 2 O-bridge of oxathianes it appeared that lithiation was easily performed with n -BuLi in the case of 1 - trans 1c and 2 - cis 3 while s -BuLi had to be used with 3 - trans.…”
mentioning
confidence: 99%
“…After the synthesis of macrocycle 8a was described, we decided to explore the chiral auxiliary proficiency of this new structural arrangement. Thus, preparation of bissulfoxide 8b was the first derivative recently described, which was successfully used as an efficient chiral acyl donor (Figure ).…”
mentioning
confidence: 99%
“…The synthesis and hydrolysis of cyclic thioacetals and ketals were described in [185][186][187][188]. 1,3-Oxathianes were used as chiral sulfides in asymmetric syntheses of mono-and diaryloxiranes [189,190] and trans-cyclopropanes [191,192] and were subjected to phosphorylation to obtain phospholipid analogs [193]. 1,3-Oxazines were reported as stereoinductors in the synthesis of optically pure compounds [194][195][196][197][198], and 6-arylbenzoxazines are potent nonsteroidal progesterone receptor agonists [199].…”
Section: Scheme 59mentioning
confidence: 99%